THE USE OF OXYTOCIN IN COMBINATION WITH UTERINE LAVAGE AS A POST-MATING TREATMENT FOR INFERTILE MARES WITH ENDOMETRITIS - F.R. , Abdul-Aziz (The Iraqi Journal of Veterinary Medicine, 2022)
Eighteen infertile multiparous mares were used in this study. They had been barren for at least 2 years and had been bred repeatedly during those years, and were 8-20 years of age. Clinical genital, and endometrial cytology and histopathological examinations revealed that the mares suffered from acute endometritis. Each mare was subjected to an intrauterine lavage with 500-1000 ml of sterile saline solution in combination with an intravenous injection of 20 I.U. of oxytocin within 12-24 hours after mating. The mares expelled most of the flushed fluid within 20 -30 minutes of oxytocin injection. Eighteen of the treated mares, 13 (72%) conceived after mating on one estrous period. Results of this study indicates that removing intrauterine fluid containing inflammatory by-products by saline lavage and inducing uterine contractions with oxytocin after mating improved conception rates in infertile mares.